Estimated pulse wave velocity is associated with all-cause mortality and cardiovascular mortality among adults with diabetes - Wu, Li-Da; Chu, Peng; Kong, Chao-Hua; Shi, Yi; Zhu, Ming-Hui; Xia, Yi-Yuan; Li, Zheng; Zhang, Jun-Xia; Chen, Shao-Liang (Frontiers in Cardiovascular Medicine, 2023)
Aims: We aim to examine the association of estimated pulse wave velocity (ePWV) with all-cause and cardiovascular mortality in patients with diabetes. Methods: All of adult participants with diabetes from the National Health and Nutrition Examination Survey (NHANES) (1999–2018) were enrolled. ePWV was calculated according to the previously published equation based on age and mean blood pressure. The mortality information was obtained from the National Death Index database. Weighted Kaplan-Meier (KM) plot and weighted multivariable Cox regression was used to investigate the association of ePWV with all-cause and cardiovascular mortality risks. Restricted cubic spline was adopted to visualize the relationship between ePWV and mortality risks. Results: 8916 participants with diabetes were included in this study and the median follow-up duration was ten years. The increment of ePWV was closely associated with increased risks of all-cause mortality (HR: 1.46, 95% CI: 1.42 - 1.51) and cardiovascular mortality (HR: 1.59, 95% CI: 1.50 - 1.68). After adjusting for cofounding factors, for every 1 m/s increase in ePWV, there was a 9% increased risk of all-cause mortality (HR: 1.09, 95% CI: 1.01 - 1.17) and 15% increased of cardiovascular mortality (HR: 1.15, 95% CI: 1.02 - 1.30). ePWV had positive linear associations with all-cause and cardiovascular mortality. KM plots also showed that the risks of all-cause and cardiovascular mortality were significantly elevated in patients with higher ePWV. Conclusions: ePWV had a close association with all-cause and cardiovascular mortality risks in patients with diabetes, which can be used as a prognostic indicator.